Basic chemical composition and bioactive compounds content in selected cultivars of buckwheat whole seeds, dehulled seeds and hulls. (May 2016) - Dziadek, Kinga; Kopeć, Aneta; Pastucha, Edyta; Piątkowska, Ewa; Leszczyńska, Teresa; Pisulewska, Elżbieta; Witkowicz, Robert; Francik, Renata
Abstract: The objective of this study was to determine the basic chemical composition and the content of selected bioactive components in hulls, dehulled seeds and whole seeds of the selected cultivars/strains of buckwheat. In the tested material the content of ash, protein, fat, fatty acids, total carbohydrates, starch, dietary fibre, resistant starch, total polyphenols, profile of polyphenols and antioxidant activity was determined. We have found that buckwheat seeds were a rich source of protein and total carbohydrates. Dehulled seeds were also a source of resistant starch. Palmitic, oleic and linoleic acids were the dominant fatty acids in all samples. Analysis of extracts from whole seeds, dehulled seeds and hulls showed that there were twenty polyphenolic compounds in the tested material. The highest content of dietary fibre and total polyphenols as well as the highest antioxidant activity were found in the hulls and the lowest one in the dehulled seeds. Because of the rich composition, buckwheat can be used in the development of new food products especially for people on gluten free diet. Highlights: Buckwheat seeds are a rich source of protein and carbohydrates. The highest content of nutrients and non-nutrient bioactive compounds was found in the hulls. Palmitic, oleic and linoleic acids were the dominant fatty acids in buckwheat seeds.